Documentation of a submerged monument using improved two media techniques - Georgopoulos, Andreas; Agrafiotis, Panagiotis (My University, 2012)
The rapid developments of technology in recent years have opened new horizons in Photogrammetry, overcoming obstacles sometimes insurmountable, reducing time and increasing accuracy of results. However, while the continuous development of close-range Photogrammetric methods for the geometric documentation of monuments on land and sea seem to go hand in hand, techniques for capturing submerged archaeological sites especially when situated at shallow depths are inadequate while application of traditional methods is impossible or uneconomical. This paper describes the improvement of two-media (through air and water) photogrammetric techniques for the documentation of a submerged archaeological site of Epidaurus, Greece, at a depth ranging from 0.5 to 2 meters. Specific reference is made to the various problems caused by the presence of water and how they were addressed. Errors in depth determination caused by waves, colour absorption and chromatic aberration are also addressed. Particular attention is given to the effects of refraction at the air/water interface on the Collinearity Condition. The various attempts are presented, analysed and evaluated. Finally, ortho-images have been generated and cross section data were collected in order to perform the documentation. © 2012 IEEE.
Keywords: camera calibration; orthophotography; refraction; two media photogrammetry